SETTLEMENT OF UNRESOLVED NOTARY OBLIGATIONS AFTER DEATH - Rahmadayanti, Erviny (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The purpose of this research is to examine and analyze the legal responsibilities of Notaries who have not completed their obligations when they die, and to examine and analyze the settlement of Notarial deeds that have not been completed after the Notary concerned dies. Meanwhile, the research method used is normative legal research, namely a method that uses primary legal material sources in the form of statutory regulations, legal theories and expert opinions, to analyze and draw conclusions about the problems used to test and study legal materials. The research results were obtained when a notary who has not completed his obligations when he dies is an obligation of his heirs because based on Article 63 paragraph 2 of Law No. 2 of 2014 concerning the Position of a Notary, the Notary Protocol is a collection of state archive documents that must be kept and maintained by a notary, which is When a notary dies, all his responsibilities end and the Notary's protocols in question must be immediately handed over to another Notary who has been appointed by the Regional Supervisory Council as the protocol holder, which is based on Article 63 paragraph (2) of Law No. 30 of 2004 regarding notaries, and secondly regarding the arrangements for completing notary work which is delayed because the notary dies, contained in Article 1 paragraph (3) of Law Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of Notaries, which reads that: